Gun dealer's daughter - Apostol, Gina (Mandaluyong City : Anvil Publishing, 2010)
A woman living in New York City recounts her youthful indiscretions as a university student in Manila whose boyfriend turned her into a communist rebel and the fatal act she committed that haunts her.
Keywords: Philippine fiction (English)